The clinical potential of gene editing as a tool to engineer cell‐based therapeutics. Issue 1 (7th February 2020) - Ashmore‐Harris, Candice; Fruhwirth, Gilbert O.
Abstract: The clinical application of ex vivo gene edited cell therapies first began a decade ago with zinc finger nuclease editing of autologous CD4 + T‐cells. Editing aimed to disrupt expression of the human immunodeficiency virus co‐receptor gene CCR5, with the goal of yielding cells resistant to viral entry, prior to re‐infusion into the patient. Since then the field has substantially evolved with the arrival of the new editing technologies transcription activator‐like effector nucleases (TALENs) and clustered regularly interspaced short palindromic repeats (CRISPR), and the potential benefits of gene editing in the arenas of immuno‐oncology and blood disorders were quickly recognised. As the breadth of cell therapies available clinically continues to rise there is growing interest in allogeneic and off‐the‐shelf approaches and multiplex editing strategies are increasingly employed. We review here the latest clinical trials utilising these editing technologies and consider the applications on the horizon.